ANALISIS DAMPAK IMPLEMENTASI MESIN FIRMWARE UPLOADING DENGAN KAPASITAS 60 INTEGRATED CIRCUIT PERMENIT PADA PERUSAHAAN IC CARD - Rachman, Fathur; Kristiawan, Timotius Anggit; Putri, Farika Tono (Politeknik Negeri Semarang, 2025)
The IC Card (IC Card) manufacturing industry still widely relies on manual methods for firmware uploading into integrated circuits, a process that involves contract labor and basic tools. This method poses several limitations including low throughput, high labor dependency, and a significant risk of human error. These issues affect overall efficiency, product quality, and operational cost. The gap identified lies in the lack of automation in the firmware uploading process, especially within local industries. To address this, the present study aims to evaluate the impact of implementing an automated Firmware Uploading Machine with a capacity of 60 integrated circuits per minute. The research methodology includes a combination of engineering design and field performance testing. The proposed system employs servo motor technology, fiber optic sensors, and PLC-based control to replace manual handling. Experimental results indicate a six-fold increase in production capacity, substantial reductions in labor requirements, and improved operational efficiency. Furthermore, a Break-even point (BEP) analysis confirms that the return on investment can be achieved in a relatively short time. In conclusion, the automated firmware uploading system offers a practical solution for improving productivity, lowering operational costs, and enabling the industrial transition towards high-efficiency and smart manufacturing environments. Keywords: Automation; BEP; efficiency; firmware uploading; integrated circuit